Synthesis, electrochemistry, and density functional theory of osmium(II) containing different 2,2′:6′,2″-terpyridines - Mateyise, Nandisiwe G. S.; Conradie, Marrigje M.; Conradie, Jeanet (MDPI, 2024)
In coordination chemistry, 2,2′:6′,2″-terpyridine is a versatile and extensively studied tridentate ligand. Terpyridine forms stable complexes with a variety of metal ions through coordination sites provided by the three nitrogen atoms in its pyridine rings. This paper presents an electrochemical study on various bis(terpyridine)osmium(II) complexes, addressing the absence of a systematic investigation into their redox behavior. Additionally, a computational chemistry analysis was conducted on these complexes, as well as on eight previously studied osmium(II)-bipyridine and -phenanthroline complexes, to expand both the experimental and theoretical understanding. The experimental redox potentials, Hammett constants, and DFT-calculated energies show linear correlations due to the electron-donating or electron-withdrawing nature of the substituents, as described by the Hammett constants. These substituent effects cause shifts to lower or higher redox potentials, respectively.
Keywords: Osmium(II); Redox potential; Electrochemistry; DFT; Terpyridine